DIKOTOMI KEILMUAN DALAM ISLAM ABAD PERTENGAHAN (Telaah Pemikiran Al-Ghazali dan Al-Zarnuji) - St. Noer Farida Laila (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2016)
The present research was aimed at describing the dichotomous attitude of Muslim medieval ulama toward the development of religious and non-religious sciences. Based on a library study on the thought of Imam al-Ghazali in his Ihya’ ‘ulum al-din, as well as the thought of al-Zarnuji in his Ta’lim almuta’allim, it was found that both ulama did not stcrikly differentiate the two sciences. Al-Ghazali saw the relation of the two sciences not in “conflict” but “independent” one each other, while al-Zarnuji devided the sciences based on their possitive aspects for Muslims’ religious life. Al-Zarnuji did not classify sciences as religious and non-religious.Kata Kunci: Dikotomi, Pemikiran Al-Ghazali, Al-Zarnuji